Vasoactive and Neuroprotective Effects of c-Jun N-Terminal Kinase Inhibitor in Rats with Chronic Cerebral Hypoperfusion; Journal of Evolutionary Biochemistry and Physiology; Vol. 59, iss. 3 - Zhilyaev S. Yu. Sergey Yurjevich; Platonova T. F. Tatjyana Fedorovna; Khlebnikov A. I. Andrey Ivanovich; Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Demchenko I. T. Ivan Timofeevich; Atochin D. N. Dmitry Nikolaevich (2023, 2023)
Title screen